Diagnosis Dan Rencana Tatalaksana Chromoblastomycosis - M. Mimbar Topik; Siti Faizah (Jurnal Ventilator, 2023)
Chromoblastomycosis is a slowly progressive granulomatous skin infection caused by several species of black fungus such as Phialophora verrucosa, Fonsecaea pedrosoi, Rhinocladiella aquaspersa and Cladosporium carrionii. A case was found of a 51-year-old patient with a main complaint of a reddish, uneven lump, occasionally itchy, but not accompanied by pain in the right arm. On anatomic pathological examination, microscopic results were obtained in the form of epidermal skin tissue preparations that appeared hyperkeratosis, acanthosis, pseudoepitheliomatous hyperplasia. Intra-epidermal abscesses were seen with an accumulation of neutrophil inflammatory cells, lymphocytes, histiocytes and groups of epitheloid cells that formed granulomas. There was no sign of malignancy. The conclusion from the results of anatomical pathology readings is that there is a fungal infection (chromoblastomycosis). Treatment is given by oral itraconazole.